2016
DOI: 10.1177/0093650215596363
|View full text |Cite
|
Sign up to set email alerts
|

Surprise! An Investigation of Orienting Responses to Test Assumptions of Narrative Processing

Abstract: This study tests theoretical assumptions about how the level of narrative engagement during exposure to a television series storyline influences how viewers process scenes within the storyline. An embodied cognition approach to information processing was applied to record and interpret psychophysiological data reflecting how viewers mentally process television program narratives. Specifically, we recorded physiological data indicating the orienting response (OR) to examine viewers’ processing of narrative surp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Other behavioral measures can serve as proxies or indicators for surprise as well, and one could, for instance, use pitch levels in verbal utterances (e.g., Ververidis et al, 2004) or facial expression (e.g., Cohn et al, 1998) as behavioral proxies for surprise. The same goes for physiological measures such as heart rate variability (Andersen et al, 2020; Sukalla et al, 2016), which nowadays can be easily measured in real-life settings in noninvasive ways.…”
Section: Discussionmentioning
confidence: 99%
“…Other behavioral measures can serve as proxies or indicators for surprise as well, and one could, for instance, use pitch levels in verbal utterances (e.g., Ververidis et al, 2004) or facial expression (e.g., Cohn et al, 1998) as behavioral proxies for surprise. The same goes for physiological measures such as heart rate variability (Andersen et al, 2020; Sukalla et al, 2016), which nowadays can be easily measured in real-life settings in noninvasive ways.…”
Section: Discussionmentioning
confidence: 99%
“…Galvanic skin response and heart rate variability are of specific interest since these measures indicate the extent to which a person is emotionally aroused. Both measures have been successfully employed in recent studies on narrative processing (e.g., Sukalla et al, 2015 ).…”
Section: Multidimensional Linguistic Cues Frameworkmentioning
confidence: 99%
“…A wealth of research has demonstrated that momentary prediction errors, or surprises, are particularly well-remembered 1,2,[7][8][9][10][11][12] and that an array of physiological and mental processes seem to underpin these memory benefits. For instance, surprise engages the dopaminergic and serotonergic midbrain systems 7,10,[13][14][15][16][17] , alters and enhances hippocampal activity 16,[18][19][20][21][22][23][24] , increases pupil dilation 7,[25][26][27][28][29] , and enhances perceptual 13,16,30,31 and attentional processing 8,[32][33][34][35][36][37][38][39] to the surprising stimulus. Surprises can be further differentiated into events that are better than expected for the agent because they signal reward (+ reward prediction error, or + signed surprise) and others that are worse than expected (-signed surprise) [40][41][42]…”
Section: Introductionmentioning
confidence: 99%